Peri-implant evaluation of osseointegrated implants subjected to orthodontic forces: results after three years of functional loading - Bruna de Rezende Marins; Suy Ellen Pramiu; Mauro Carlos Agner Busato; Luiz Carlos Marchi; Adriane Yaeko Togashi (Dental Press Editora, 2016)
ABSTRACT Objective: The objective of this study was to clinically and radiographically assess the peri-implant conditions of implants used as orthodontic anchorage. Methods: Two groups were studied: 1) a test group in which osseointegrated implants were used as orthodontic anchorage, with the application of 200-cN force; and 2) a control group in which implants were not subjected to orthodontic force, but supported a screw-retained prosthesis. Clinical evaluations were performed three, six and nine months after prosthesis installation and 1- and 3-year follow-up examinations. Intraoral periapical radiographs were obtained 30 days after surgical implant placement, at the time of prosthesis installation, and one, two and three years thereafter. The results were compared by Kruskal-Wallis test. Results: There was no statistically significant difference in clinical probing depth (p = 0.1078) or mesial and distal crestal bone resorption (p = 0.1832) during the study period. After three years of follow-up, the mean probing depth was 2.21 mm for the control group and 2.39 mm for the test group. The implants of the control group showed a mean distance between the bone crest and implant shoulder of 2.39 mm, whereas the implants used as orthodontic anchorage showed a mean distance of 2.58 mm at the distal site. Conclusion: Results suggest that the use of stable intraoral orthodontic anchorage did not compromise the health of peri-implant tissues or the longevity of the implant.